THE STUDENTS’ VIEWS ON THE INDONESIA’S NON-MUSLIM LEADER’S PHENOMENON IN AISYIYAH UNIVERSITY YOGYAKARTA - Zuhdi, M Nurdin; Setiawan, Iwan; Nawawi, M Anwar; Zubad, Muhammad; Iwanudin, Iwanudin; Asnawi, Habib Shulton (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
The phenomenon of non-Muslim leaders in Indonesia has given pros and cons in society. Those pros and cons do not only appear among the general public but also appear among students. This study analyzes the views of Muslim students at ‘Aisyiyah University Yogyakarta (UNISA) about the phenomenon of non-Muslim leaders in Indonesia. This research became important considering the last two issues that have emerged in the study of Islam in Indonesia, namely religious intolerance and moderation in few years. The type of this research is mixed qualitative-quantitative field research. The research findings show that there are two kinds of views of UNISA Muslim students about non-Muslim leaders; First, Muslim students who disagree about non-Muslim leaders. They argue that choosing a leader must be based on his/her religion first. This group believed that Islam is the main non-negotiable requirement for someone who wants to run for a leader. Some of them even firmly stated that choosing a non-Muslim leader is categorized as haram. Second, Muslim students agree and do not object to the existence of non-Muslim leaders. The second group believed that religion is not an absolute issue as the requirement for a person who wants to become a leader. This second group argues that track records are more important than religion or ethnicity. The educational background of students also influences their views. Students with religious education backgrounds tend to be more accepting of differences. On the other hand, students who have a general educational background tend not to easily accept differences. Therefore, it can be concluded that the better a person understands religion, the more tolerant of differences he/she will be.